Multi-physics safety model based on structure damage for lithium-ion battery under mechanical abuse - Yiding, Li; Wenwei, Wang; Cheng, Lin; Xiaoguang, Yang; Fenghao, Zuo (Journal of cleaner production, 2020)
The failure of lithium-ion batteries under mechanical abuse is a multi-physical process involving mechanical failure, electrochemical degradation, internal electric short circuit, thermal runaway and structure damage. To gain a fundamental understanding of the failure mechanisms, in this work we propose a mechanical-electrochemical-thermal coupling model based on structure damage to study the failure behavior of lithium-ion battery under mechanical abuse in hard short-circuit stage from the real 3D structure and the whole battery level. The failure elements in the mechanical model are transferred into failure geometry and combined with the deformed cylindrical lithium-ion battery body. Then the short-circuit thermal power is calculated by the short-circuit model and sent to the thermal model. The electrochemical model outputs the terminal voltage and the electrochemical heat generation rate to the short-circuit model and the thermal model, respectively. The thermal model calculates cell temperature and feeds it back to the electrochemical model. The coupling model points out the fact that the internal short circuit heat is the main heat source during the short time of hard short-circuit stage under mechanical abuse. Furthermore, the coupling multi-physics model provides fundamental insights into the mechanisms of battery failure under mechanical abuse condition and can accelerate the analysis process which helps to understand the failure phenomenon in the future researches. •This paper proposes a coupling failure model for battery under mechanical abuse.•The mechanical-electrochemical-thermal model is based on the structure damage.•The multi-physics model can simulate the battery failure under mechanical abuse well.